Material loss at the femoral head taper: a comparison study of the Exeter metal-on-polyethylene and contemporary metal-on-metal total hip arthroplasty. (October 2018) - Langton, D. J.; Wells, S. R.; Joyce, T. J.; Bowsher, J. G.; Deehan, D.; Green, S.; Nargol, A. V. F.; Holland, J. P.
Abstract : Aims: There are limited published data detailing the volumetric material loss from tapers of conventional metal-on-polyethylene (MoP) total hip arthroplasties (THAs). Our aim was to address this by comparing the taper wear rates measured in an explanted cohort of the widely used Exeter THA with those measured in a group of metal-on-metal (MoM) THAs. Patients and Methods: We examined an existing retrieval database to identify all Exeter V40 and Universal MoP THAs. Volumetric wear analysis of the taper surfaces was conducted using previously validated methodology. These values were compared with those obtained from a series of MoM THAs using non-parametric statistical methodology. A number of patient and device variables were accounted for using multiple regression modelling. Results: A total of 95 Exeter MoP and 249 MoM THAs were examined. The median volumetric loss from the MoM cohort was over four times larger than that from the MoP cohort (1.01 mm 3 vs 0.23 mm 3, p < 0.001), despite a significantly shorter median period in vivo for the MoM group (48 months vs 90 months, p < 0.001). Multiple regression modelling indicated that the dominant variables leading to greater female taper material loss were bearing diameter (p < 0.001), larger female taper angles (p < 0.001), and male titanium stem tapers (p < 0.001). Conclusion: Consistent with the long-term clinical success of the device, the volumetric material loss from Exeter femoral head tapers was, in general, small compared with that from larger-diameter MoM head tapers. Cite this article: Bone Joint J 2018;100-B:1310–9.